Tammela Lunkaan kylä, jouluvalko yleisön edessä - Aaltonen, Esko
fyysinen kuvaus: vaaka
Keywords: kalendaariperinne; joulu; jouluvalkot; karnevalismi; uskonnolliset juhlat; tapaninpäivä; taruolennot; naamiaispuvut; nuket; asut; yleisö; lastenvaatteet; puvut; Suomi, Tammela, Lunkaa, Tammela, Lunkaa